Analisis Peramalan Time Series dengan Exponential Smoothing Kejadian Hipertensi di Puskesmas Poned Balowerti 2022-2026 - Nindya Puspita Sari; Mohamad Anis Fahmi (Ficco Public Health Journal, 2024)
Background: Hypertension is a non-communicable disease often referred to as the silent killer. Hypertension is a health problem that needs attention, this is the high morbidity and mortality due to hypertension. The aim of this research is to predict the incidence of hypertension in the next year in Balowerti PONED Community Health Centre. Methods: Conducting research at Balowerti PONED Community Health Centre UPTD on Jalan Balowerti V, Balowerti Village, Kota District, Kediri City. Data collection will be conducted from 10 January to 29 January 2022, starting from 07.00 to 14.30 WIB. Predicting the incidence of hypertension can be used to determine plans for the management and prevention of hypertension and to reduce morbidity due to hypertension. Data analysis was performed using RStudio software version 372. Results: There was a decrease in the incidence of hypertension in 2020 and 2021. The triple exponential smoothing model gave the smallest sum-square error (SSE) of 290,767.4. Therefore, the triple exponential smoothing model was used as the forecasting model. The forecasting results show a downward trend in 2022-2026. Conclusion: Despite the predicted decrease, the public is expected to play an active role in hypertension prevention efforts to reduce the risk of other health problems due to hypertension in the future.